2015
DOI: 10.5539/apr.v7n6p85
|View full text |Cite
|
Sign up to set email alerts
|

Classical Definitions of Gravitation, Electricity and Magnetism

Abstract: In further demonstration of simultaneous existence of the atom as wave and particle, we reproduce values of a number of physical constants using the classical mass equation hϑ = mc 2 . Most, possibly all, physical constants are coefficients of linear correlations of parameters of the intrinsic electromagnetic (e-m) oscillation that defines the atom; for example: (i) angular frequency per unit radius ω/r correlates with rotational strain τ to produce the effect identified with atomic mass; (ii) the atomic wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…It became obvious that the atom must be a waveonly electromagnetic resonator with characteristic SHM parameters, values of which corroborated observational data, Obande (2015a); results of atomic mass investigation sealed the case for the wave-only atom, Obande (2016a). We proceeded to investigate possibility of inter-relationships between the physical parameters and found that they correlate linearly y = ax k where the coefficient reproduces established value of the fundamental constant, Obande (2015bObande ( ), (2017, it led to an investigation of the exponent k, the result of which is presented herein. This series of investigations is informed by sheer curiosity having been concerned, since college, for non-availability nor, indeed, mention of absolute atomic mass in the literature.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It became obvious that the atom must be a waveonly electromagnetic resonator with characteristic SHM parameters, values of which corroborated observational data, Obande (2015a); results of atomic mass investigation sealed the case for the wave-only atom, Obande (2016a). We proceeded to investigate possibility of inter-relationships between the physical parameters and found that they correlate linearly y = ax k where the coefficient reproduces established value of the fundamental constant, Obande (2015bObande ( ), (2017, it led to an investigation of the exponent k, the result of which is presented herein. This series of investigations is informed by sheer curiosity having been concerned, since college, for non-availability nor, indeed, mention of absolute atomic mass in the literature.…”
Section: Resultsmentioning
confidence: 97%
“…In 2-D it gives four field envelopes distributed at the apices of a square plane quite reminiscent of orbital; in 3-D it gives a regular octagon. Now, dimensional analysis reveals closely similar units for ε and λ c, Obande (2015b), (2017) that manifests λ c ; the former gives rise to electrical effects and the latter to spatial dimension. It underscores the crucial role electro-geometry plays in defining the FC, chemical reactivity and, indeed, geometry of all natural forms.…”
Section: Fundamental Constants As 3-d Spacetime Slicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observe as follows: i) radioactivity is caused exclusively by changes in tensile properties of the boson field that encases fermionic matter exactly as shown in Figure 1; in other words, the wave component of the atom exercises significant control over the particulate matter component likewise, the cosmic vacuum field exercises similar control over its material cosmological content; ii) Figure 4 pinpoints spontaneous radioactivity at At, τ * w = 2.14, i.e., 214%; iii) Figure 5 facilitates visualization of the stepwise process of nuclear instability that leads to radioactivity. Discernible evidence of instability commences at Ru, Z n = 70, where a change becomes noticeable in the τ * w /Z n gradient, the change progresses gradually up to Xe, Z n = 80 where a sudden jump occurs signifying considerable instability albeit insufficient to initiate spontaneity which eventually occurs at At, Z n = 111, Obande (2015c). The quotient τ/(ω/r) denotes electrostatics effect, it manifests atomic mass, Obande (2016a), it would account for m-e packet ejection at spontaneity as reflected in the staggered mass distribution.…”
Section: Radioactivity and Stellar Explosion/supernovamentioning
confidence: 99%
“…Thus, spin in QM admits of quantized (classical) angular momentum but rejects (quantized) classical physical rotation, it makes it a bit challenging to rationalize QM's spin with observational evidence see, for instance, Moskowitz (2014) and Siegel (2017). One would have expected that by now there should be no doubt regarding universality of scale-free spin in the context of physical rotation; it comes quite naturally in analysis of the classical quantum state, Obande (2015bObande ( , 2015cObande ( , 2016a and in observational cosmology, Rubin (2000). Indeed, existence as we know it in terms of say, gravitation, magnetism and random (thermal) motion would cease without scale-free physical rotation of matter waves, Obande (2017a).…”
Section: Radioactivity and Stellar Explosion/supernovamentioning
confidence: 99%